Effects of ultrasound-guided regional anesthesia in cardiac surgery: a systematic review and network meta-analysis - Burhan Dost; Alessandro De Cassai; Eleonora Balzani; Serkan Tulgar; Ali Ahiskalioglu (BMC Anesthesiology, 2022)
Abstract Background The objective of this systematic review and network meta-analysis was to compare the effects of single-shot ultrasound-guided regional anesthesia techniques on postoperative opioid consumption in patients undergoing open cardiac surgery. Methods This systematic review and network meta-analysis involved cardiac surgical patients (age > 18 y) requiring median sternotomy. We searched PubMed, EMBASE, The Cochrane Central Register of Controlled Trials (CENTRAL), Scopus, and Web of Science. The effects of the single-shot ultrasound-guided regional anesthesia technique were compared with those of placebo and no intervention. We conducted a risk assessment of bias for eligible studies and assessed the overall quality of evidence for each outcome. Results The primary outcome was opioid consumption during the first 24 h after surgery. The secondary outcomes were pain after extubation at 12 and 24 h, postoperative nausea and vomiting, extubation time, intensive care unit discharge time, and length of hospital stay. Fifteen studies with 849 patients were included. The regional anesthesia techniques included pecto-intercostal fascial block, transversus thoracis muscle plane block, erector spinae plane (ESP) block, and pectoralis nerve block I. All the regional anesthesia techniques included significantly reduced postoperative opioid consumption at 24 h, expressed as morphine milligram equivalents (MME). The ESP block was the most effective treatment (-22.93 MME [-34.29;-11.56]). Conclusions In this meta-analysis, we concluded that fascial plane blocks were better than placebo when evaluating 24 h MMEs. However, it is still challenging to determine which is better, given the paucity of studies available in the literature. More randomized controlled trials are required to determine which regional anesthesia technique is better. Trial registration PROSPERO; CRD42022315497.